The Application of Artificial Intelligence in Accounting Reporting within the Banking Sector - Sibagariang, Ricardo Parulian (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2025)
Artificial Intelligence (AI) has emerged as a significant innovation supporting digital transformation in the banking sector. In the context of financial reporting, AI offers effective solutions to enhance efficiency, accuracy, and transparency in the reporting process. This study aims to analyse the role of AI in supporting financial reporting in the banking sector, including its benefits and the challenges faced. Using a literature review approach, this research reveals that AI technology enables banks to automate routine tasks, detect anomalies in financial reports, and provide predictive data to support strategic decision-making. However, the implementation of AI also presents challenges such as the need for substantial investment, system integration with existing infrastructure, and compliance with regulations. This study concludes that the application of AI has the potential to revolutionize financial reporting practices, providing significant competitive advantages while driving efficiency and security in banking operations.